Estudo de produtos naturais e derivados sintéticos buscando inibidores seletivos das catepsinas L e V - Marques, Emerson Finco (2011)
The present work describes the search of bioactive secondary metabolites in plant species of genus Zanthoxylum and synthetic derivatives seeking specific inhibitors of cathepsins L and V. The natural products are involved in approximately 50% of all drugs marketed. Cathepsins represent a class of enzymes that has the primary function of randomly degrade proteins at lysosomes, but are also involved in different pathologies, such as, atherosclerosis, rheumatoid arthritis, osteoporosis and various cancers. This work was carried out monitoring Zanthoxylum extracts by fluorimetric assays and by Highperformance liquid chromatography (HPLC). Among the species studied, the most promising extracts were methanol and dichloromethane extracts of Zanthoxylum acuminatum, the latter being selected for isolation. The chromatographic methodology afforded the isolation of a triterpene: lupeol (1), the coumarins umbelliferone (2), heradenol (3), nordentatin (4), anisocoumarin (5), derivated of 6´,7´-epoxy-7-geranyloxycoumarin (6); canthinonic alkaloids 5-methoxycantin-6-one (7), 4,5-dimehoxycantin-6-ona (8); β-carboline alkaloid; 7-hydroxi-1-ethyl-β-carboline (9); and acridone alkaloid arborinine (10). All were tested at concentration of 25 mM and coumarin 5 inhibited over 50%, showing more activity and selective against cathepsin L. The value potency (IC50) of this compound was 30 μM for cathepsin L and 102 μM for cathepsin V. Furthermore, were determined the potency values, selectivity and mechanism of action acridones alkaloids isolated from Swinglea glutinosa, N-aryl anthranilic acids, synthetic acridone alkaloids and a series of alkaloids 4-quinoline-2-substituted. The most promising compound was the alkaloid acridone AC_05 with a IC50 of 0.5 μM and Ki of 0.18 μM. Moreover, the compound AC_05 presented as a competitive inhibitor against both cathepsins, which is consistent with the interaction model proposed by molecular modeling.